Hybrid learning environments: It’s all about ecology - Green, Jenny; Carvalho, Lucila; Sheridan, Nicolette (Proceedings of the International Conference on Networked Learning, 2024)
Technology-enhanced learning has been part of higher education health contexts for nearly three decades, but since the recent Covid-19 pandemic specific challenges emerged, requiring learning design reconfigurations to facilitate continuity of student learning. The pandemic calls for a deeper understanding of how technology can promote connections, active participation and knowledge building in higher education health contexts. Identifying what is currently occurring and considering potential innovations requires a move towards a nuanced understanding of the ecology of complex elements contributing to productive networked learning in these contexts. This multiple-case study doctoral research project includes four undergraduate health courses at a New Zealand university, in the disciplines of nursing, social work, and bioscience. Drawing on the Activity Centred Analysis and Design (ACAD) framework, the research explores the influence of course design elements, such as social arrangements, learning space formats, learning tasks, on learning activity, taking a systematic approach to the analysis. In this paper, we report on initial observations and interviews with students involved in diverse hybrid learning environments, in order to identify how innovative learning designs are supporting students’ agency and active engagement.